Transforming Early Childhood in England : Towards a Democratic Education - Cameron, Claire (UCL Press, 2020)
Transforming Early Childhood in England: Towards a Democratic Education offers a critique of the current system of early childhood care and education in England, and proposes policy change to enable young children's universal right to education. Combining criticism and hope, the book calls for democratic provision, where all learning by all children is recognised, educators are respected, and pedagogy is shaped by young children's learning.